The soil effect on the seismic behaviour of reinforced concrete buildings - Yon, Burak; Calayir, Yusuf (Techno-Press, 2015)
This paper investigates the soil effect on seismic behaviour of reinforced concrete (RC) buildings by using the spread plastic hinge model which includes material and geometric nonlinearity of the structural members. Therefore, typical reinforced concrete frame buildings are selected and nonlinear dynamic time history analyses and pushover analyses are performed. Three earthquake acceleration records are selected for nonlinear dynamic time history analyses. These records are adjusted to be compatible with the design spectrum defined in Turkish Seismic Code. Interstory drifts and damages of selected buildings are compared according to local soil classes. Also, capacity curves of these buildings are compared with maximum responses obtained from nonlinear dynamic time history analyses. The results show that, soil class influences the seismic behaviour of reinforced concrete buildings, significantly.
Keywords: local soil class; spread plastic hinge; interstory drift; pushover analysis; time history analysis